Potentially modifiable lifestyle factors, cognitive reserve, and cognitive function in later life: A cross-sectional study. - Linda Clare; Yu-Tzu Wu; Julia C Teale; Catherine MacLeod; Fiona Matthews; Carol Brayne; Bob Woods; CFAS-Wales study team (PLoS Medicine)
Background Potentially modifiable lifestyle factors may influence cognitive health in later life and offer potential to reduce the risk of cognitive decline and dementia. The concept of cognitive reserve has been proposed as a mechanism to explain individual differences in rates of cognitive decline, but its potential role as a mediating pathway has seldom been explored using data from large epidemiological studies. We explored the mediating effect of cognitive reserve on the cross-sectional association between lifestyle factors and cognitive function in later life using data from a population-based cohort of healthy older people. Methods and findings We analysed data from 2,315 cognitively healthy participants aged 65 y and over in the Cognitive Function and Ageing Study Wales (CFAS-Wales) cohort collected in 2011-2013. Linear regression modelling was used to investigate the overall associations between five lifestyle factors-cognitive and social activity, physical activity, diet, alcohol consumption, and smoking-and cognition, adjusting for demographic factors and chronic conditions. Mediation analysis tested for indirect effects of the lifestyle factors on cognition via cognitive reserve. After controlling for age, gender, and the presence of chronic conditions, cognitive and social activity, physical activity, healthy diet, and light-to-moderate alcohol consumption were positively associated with cognitive function, together accounting for 20% (95% CI 17%-23%) of variance in cognitive test scores. Cognitive reserve was an important mediator of this association, with indirect effects via cognitive reserve contributing 21% (95% CI 15%-27%) of the overall effect on cognition. The main limitations of the study derive from the cross-sectional nature of the data and the challenges of accurately measuring the latent construct of cognitive reserve. Conclusions Cross-sectional associations support the view that enhancing cognitive reserve may benefit cognition, and maintenance of cognitive health may be supported by a healthy and active lifestyle, in later life.